The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1029/2019gl085889
|View full text |Cite
|
Sign up to set email alerts
|

Structural Transitions in MgSiO3 Glasses and Melts at the Core‐Mantle Boundary Observed via Inelastic X‐ray Scattering

Abstract: The structural adaptation in MgSiO 3 melts under compression up to 130 GPa is the key to revealing the origins of the pronounced negative buoyancy of the melts at the core-mantle boundary (CMB). A full understanding of the melt densification requires study of the pressure-induced changes in the bonding configuration around oxygen at the CMB, which has proven to be difficult to measure. Here, the experimental breakthrough in O K-edge inelastic X-ray scattering enables collection of the spectra of MgSiO 3 glasse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 43 publications
2
13
0
Order By: Relevance
“…DFT has been used in many studies to complement experimental investigations of environmentally important materials: for example, the surface adsorption behavior, the metal intercalation tendency into clay minerals, , the electronic structure of high-pressure minerals, and electronic transition spectroscopy (X-ray Raman scattering, X-ray absorption, optical properties, etc. ). ,, We established detailed calculation conditions by referring to these previous studies with suitable adjustments (see also Section 2 in the Supporting Information). Electronic structures used for structure optimization and for determining E B and E vib were calculated using CASTEP .…”
Section: Methodsmentioning
confidence: 99%
“…DFT has been used in many studies to complement experimental investigations of environmentally important materials: for example, the surface adsorption behavior, the metal intercalation tendency into clay minerals, , the electronic structure of high-pressure minerals, and electronic transition spectroscopy (X-ray Raman scattering, X-ray absorption, optical properties, etc. ). ,, We established detailed calculation conditions by referring to these previous studies with suitable adjustments (see also Section 2 in the Supporting Information). Electronic structures used for structure optimization and for determining E B and E vib were calculated using CASTEP .…”
Section: Methodsmentioning
confidence: 99%
“…[22, 23] and references therein). Advances in element‐specific nonresonant inelastic X‐ray scattering (IXS) revealed the densification of MgSiO 3 glass, suggesting the formation of tricluster oxygen and related changes in medium‐range structures above 20 GPa 8 and the reduction of O–O distance up to 130 GPa 24,25 . However, overlap among the binary correlation functions in the pair distribution functions (from X‐ray and neutron scattering) of oxide glasses is more prevalent at elevated pressure conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, pioneering elastic, inelastic X-ray, and neutron scattering studies have shown pressure-induced structural transitions in the glass (e.g., Refs. [8,[18][19][20][21][22][23][24]), suggesting an increase in coordination numbers for Si and Mg at relatively low-pressure conditions up to ∼20 GPa 18,19 ; scattering studies of MgSiO 3 glasses above 100 GPa revealed pressure-induced changes in elastic wave velocities and systematic shift in the first peak of the structure factor above 100 GPa, implying the major structural changes in the amorphous netwokrs (see Refs. [22,23] and references therein).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, the calculation parameters were referred from previous studies and adjusted in the context of calculation efficiency: the surface adsorption behavior, [1][2][3] the metal intercalation tendency into clay minerals, [4][5] the electronic structure of high-pressure minerals, [6][7][8][9][10][11] and the electronic transition spectroscopy (X-ray Raman scattering, X-ray absorption, and optical properties, etc.). [6][7][10][11] As summarized in the manuscript, the adsorption behaviors of atmospheric Hg on ice were explored via DFT calculations with following conditions: the ultrasoft pseudopotential, the Perdew-Burke-Ernzerhof (PBE) exchange-correlation functional with Tkatchenko-Scheffler (TS) dispersion correction, the 400 eV of cut-off energy, and the Γ point Brillouin zone sampling. [12][13][14] When using the non-localized plane-wave basis sets (e.g., WIEN2k [15][16] and CASTEP 12 ), the accuracy is determined primarily from the cutoff energy and the number of irreducible k points (i.e., the density of Monkhorst-Pack grid).…”
Section: Si2 Details For Electronic Structure Calculationsmentioning
confidence: 99%